Stock structure of the blue threadfin (Eleutheronema tetradactylum) across northern Australia derived from life-history characteristics - Ballagh, A.; Welch, D.; Newman, Stephen; Allsop, Q.; Stapley, J. (Elsevier BV, 2012)
Life history characteristics were used to determine the stock structure of the polynemid Eleutheronema tetradactylum across northern Australia. Growth, estimated from back-calculated length-at-age from sagittal otoliths, and length at sex change were estimated from samples collected from 12 different locations across western, northern and eastern Australia between 2007 and 2009. Comparison of back-calculated length-at-age, growth and length at sex change between locations revealed significant variation in the life-history characteristics of E. tetradactylum across northern Australia, with significant differences detected in 43 of 45 location comparisons. Differences in otolith size relative to fish length also existed amongst locations. No differences in other morphometric relationships were detected. The results of this study provide evidence for a high degree of spatial population subdivision for E. tetradactylum across northern Australia, the finding of which has implications for E. tetradactylum fisheries throughout its range, and provides a biological basis for spatial management of the species in Australia. © 2012 Elsevier B.V.